HKI dan UU Pemajuan Kebudayaan - Agus Sardjono (JIPRO: Journal of Intellectual Property, 2019)
The Constitution 1945 has obligated government to advance culture. Symphonizing Intellectual Property in the advancement of culture must be a major project burdened by government to realize it. The concept of Intellectual Property Rights  has been aimed to giving rewards to creative people who maintain momentum by cultural promotion act 2017 enactment. As aconsequence, goverment and society are encourage to be united to execute the law in order to realize the cultural advance in Indonesian in regard to the concept of Intellectual Property Rights. It is becoming the main idea of this writing. Furthermore, this writing is provided accordance with normative legal research method which thr research focused on law as a rule